A new classification of the Chirostyloidea (Crustacea: Decapoda: Anomura) - Schnabel, Kareen E.; Ahyong, Shane T. (Zootaxa, 2010)
The high level classification of the Chirostyloidea Ortmann, 1892, is reviewed. Eumunididae Milne-Edwards & Bouvier, 1900, is resurrected for two genera formerly placed in the Chirostylidae Ortmann, 1892, Eumunida Smith, 1883, and Pseudomunida Haig, 1979, based on shared characteristics such as the dorsal carapace striation, presence of supraocular spines of the rostrum, dentition of the mandible, presence of an epipod and an annulated exopod flagellum of maxilliped 1. Three families are now included in the Chirostyloidea: Chirostylidae, Eumunididae and Kiwaidae. Diagnoses are provided for each family as well as a key to the families. The fossil record of the Chirostyloidea is discussed, with putative records of Eumunida in the fossil record referred to the galatheid genus Sadayoshia Baba, 1969.